PENGARUH ETIKA SOSIAL TERHADAP PRESTASI BELAJAR PESERTA DIDIK: DI MTS NEGERI 2 CIAMIS - Prakasa, Hari; Anwari, Doni (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
This research aims to know the influence of social attitudestoward the learning achievement of students in the Islamic JuniorSchool 2 Ciamis. This research uses descriptive quantitative method.While, the research data had gotten from the questioner, interview anddocument. The result of this research is the influence of social attitudestoward the learning achievement of students has a positive andsignificant influence which is classified as median, it is approved by thepoint of 0.49 is on the interval 0.41 – 0.60 which is categorized asmedian and also t-count is bigger than t-tabble, 3.2242 points biggerthan 2,0315, then, the social attitudes have a positive and significantcorrelation toward the students’ learning achievement about 24.01%,mean while 75.99% is made from another factors beyond this research,they could be family, friends, environment, and social factors.